The Application of Airlines' Liability for Flight Delays (A Study of Airlines at Sorong Deo Airport) - Dwi Hari Prasetyawati; Hasriyanti Hasriyanti; Masrifatun Mahmudah (Journal of Law Justice (JLJ), 2026)
This study aims to identify and analyze the liability of air carriers for the payment of fines for flight delays under Law No. 1 of 2009 on Aviation, as well as the implementation of compensation payments by airlines operating at Sorong City’s Deo Airport. The research method employed is normative legal research using a statutory approach. The data types utilized include primary and secondary data. The Novelty of this study lies in its focus on the concrete implementation of airlines’ liability in providing compensation for flight delays at Sorong City Deo Airport. Furthermore, it examines the gap between legal regulations (das sollen) and their practical implementation (das sein), particularly regarding legal certainty and the protection of passengers’ rights in cases of flight delays. The research findings indicate that airlines are responsible for providing compensation for losses incurred by passengers due to flight delays in accordance with statutory regulations. However, the carrier may be exempted from liability if it can prove that the delay was not caused by its negligence. Additionally, passengers who suffer losses due to flight delays have legal recourse by filing a claim or lawsuit against the airline. Compensation is actively provided by authorized parties, such as the general manager, station manager, or staff designated by the airline. The conclusion indicates that the airline’s liability for flight delays is clearly regulated in Law No. 1 of 2009 on Aviation and Minister of Transportation Regulation No. 77 of 2011, specifically Article 10(a) through (c), so that the provision of compensation to passengers is a legal obligation that must be fulfilled by the air carrier in accordance with applicable regulations.